Early effects of neutering on energy expenditure in adult male cats. - Alfreda Wei; Andrea J Fascetti; Kyoungmi Kim; Ada Lee; James L Graham; Peter J Havel; Jon J Ramsey (PLoS ONE, 2014)
The initial cause of post-neutering weight gain in male cats is not entirely known. There is evidence that energy intake (EI) increases rapidly post-neutering, but it is not clear if neutering also decreases energy expenditure (EE) prior to weight gain. Thus, the purpose of this study was to determine if a decrease in EE contributes to the initial shift toward positive energy balance in neutered male cats. To determine the influence of neutering on EE independent of changes in EI and body weight (BW), male cats were fed at their pre-neutering maintenance EI and EE was measured at 4 days pre-neutering, 3-4 days post-neutering, and 9 days post- neutering. Ad libitum food access was then provided for 6 months. Body composition was measured and blood samples collected for serum chemistry at pre-neutering and 7 days, 13 days and 6 months post-neutering. Total energy expenditure (TEE) adjusted for lean body mass (LBM) did not change in cats from pre-neutering to 9 days post-neutering. However, TEE adjusted for BW and resting energy expenditure adjusted for either LBM or BW showed a small, but significant (P<0.05) increase from pre-neutering to 9 days post-neutering. When allowed free choice food access, cats showed significant increases of food intake (FI) and BW. Circulating concentrations of ghrelin increased, while adiponectin levels decreased following neutering. The results of this study indicate that initial post-neutering weight gain in male cats results from increased FI and not decreased EE. Long-term control of FI should be initiated after neutering to prevent hyperphagia and weight gain in male cats.